Analisis Kualitas Pelayanan BPJS Ketenagakerjaan Tanjung Morawa Menggunakan Model Servqual - Isna Nurul Ain; Fauzi Arif Lubis (Universitas Muhammadiyah Surabaya, 2023)
ABSTRAKBPJS Ketenagakerjaan is one of the organizations that provides social security services for all workers in Indonesia. The purpose of this study is to find out how good the quality of public services at BPJS Ketenagakerjaan Tanjung Morawa uses the SERVQUAL (Service Quality) method which consists of five dimensions, namely the response dimension ( responsiveness), empathy (empathy), physical evidence (tangible), assurance (guarantee), and reliability (reliability). The research method uses a qualitative approach with a descriptive research type with data collection through interviews, observation and documentation. The results of the study show that the quality of service at the Tanjung Morawa Employment BPJS is in the good category. This can be seen from the good fulfillment of four of the five dimensions of SERVQUAL, namely the dimensions of tangible, reliability, assurance, and responsiveness. While on the dimension of empathy, the results of the study show that the fulfillment of this dimension is still not good.Keywords: Public services; Service quality; BPJS Ketenagakerjaan